Effect of Newborn Piglet’s Skin Extract on Burn Wound Healing - Shkodovskaya, N. Yu.; Galchenko, S. E.; Mamontova, A. V.; Sandomirsky, B. P. (Problems of Cryobiology and Cryomedicine, 2004)
A comparative study of the effect of newborn piglet’s skin extract (NPSE) and placenta extract (PE) on the burn healing has been carried-out in rats. A subcutaneous NPSE injection into the wound area was shown to reduce the wound cell infiltration, to accelerate the granular tissue formation, resulting in quicker wound healing in comparison with the control (without NPSE) and with subcutaneous PE introduction. Studying the peculiarities of wound healing process with applying NPSE and PE revealed a higher rate in regeneration under NPSE effect.